Protective role of ginsenoside Rg1 in the dynamic progression of liver injury to fibrosis: a preclinical meta-analysis - Dan, Lijuan; Li, Xiuyan; Chen, Shuanglan; You, Xiaojie; Wang, Dong; Wang, Tianyuan; Li, Jia; Liu, Wenping; Mu, Jie; Feng, Quansheng (Frontiers in Pharmacology, 2025)
BackgroundThe pathological progression from liver injury to fibrosis is a hallmark of liver disease, with no effective strategies to halt this transition. Ginsenoside Rg1 has demonstrated a range of hepatoprotective properties; however, systematic preclinical evidence supporting its therapeutic potential for liver injury and fibrosis remains limited. Purpose. This study evaluated the efficacy and underlying mechanisms of ginsenoside Rg1 in animal models of liver injury and fibrosis, and providing a basis for future clinical investigation.MethodsA systematic review was conducted on preclinical studies published in PubMed, Web of Science, and Embase databases up to 1 August 2024, adhereing to rigorous quality standards. The methodological quality was assessed using SYRCLE’s risk of bias tool. Meta-analysis and subgroup analysis were performed using Revman 5.4 software, while publication bias was evaluated through funnel plots and Egger’s test in STATA 15.0 software. Additionally, a time-dose interval curve was utilized to assess the dose-response relationship and identify the effective dose of ginsenoside Rg1 for treating liver injury and fibrosis.ResultsTwenty-four trials involving 423 animals were included. The findings indicated that ginsenoside Rg1 significantly improved liver function markers (ALT and AST), reduced pathological indicators associated with liver injury and fibrosis, and lowered liver fibrosis-related markers (α-SMA, HYP, and PCIII). Furthermore, it exhibited beneficial effects on mechanistic indicators of inflammation, oxidative stress, and apoptosis, compared to the control group (P < 0.05). Time-dose interval analysis revealed that the effective dose range of ginsenoside Rg1 was between 4 and 800 mg/kg/d.ConclusionRg1 at a dose of 4–800 mg/kg/d mitigates the progression of liver injury to fibrosis via anti-inflammatory, antioxidative, and anti-apoptotic pathways.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD 42024557878.